Going cashless: Exploring the students' preferences towards the level of acceptance and usage of mobile wallets at PLM Business School - Domingo, Patricia Mae A. Manansala, Kyle Danielle D. Pelayo, Shianne, San Juan, Benjamin B. Yanga, Arvin M. 4 0 16; 5 (2023)
ABSTRACT In the recent years, the world has witnessed a significant shift towards a cashless society, driven by technological advancements and changing consumer behaviors. As traditional forms of payment such as cash and cards are gradually being replaced by digital alternatives, it becomes crucial to understand how different segments of society, particularly students, perceive and adopt these emerging payment methods. This study aims to explore the preferences of students at PLM Business School regarding the level of acceptance and usage of mobile wallets. A modified UTAUT model was used as a conceptual framework. Data were collected from 256 PLM Business School students. The results showed that personal innovativeness, perceived ease of use, perceived usefulness, perceived security, and social influence significantly influence the acceptance and usage of mobile wallets. The findings aim to provide valuable insights for educational institutions, financial institutions, and mobile wallet providers, enabling them to develop strategies that promote the seamless integration of mobile wallets into the daily lives of students, fostering a digitally empowered future.
Business Research: (BSBA major in Marketing) - Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2